Personality and Group Performance: The Importance of Personality Composition and Work Tasks - KRAMER, Amit (Institutional Knowledge at Singapore Management University, 2014)
We examine whether group members’ Big Five personality composition (variability, minimum, and maximum) affects the group’s performance. We employed an experimental design where participants were paid based on their performance in two different group-based experimental tasks: an additive task (where group performance is based on the sum of efforts of all group members) and a conjunctive task (where group performance is based on the performance of the weakest group member). Results indicate that variability in extraversion is positively related to group performance on the additive task but not on the conjunctive task. Conversely, neuroticism maximum score is negatively related to group performance on the conjunctive task but not on the additive task.